2010
DOI: 10.1016/j.ijgo.2010.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of training in the use and generation of evidence on episiotomy practice and perineal trauma

Abstract: ObjectiveTo examine episiotomy practices before and after a multi-component intervention designed to support the use and generation of research evidence in maternal and neonatal health care.MethodsSet in 9 centers across 4 Southeast Asian countries, a retrospective survey was performed for 12 recommended pregnancy/childbirth practices and 13 outcomes of women in each center before and after intervention. Qualitative interviews were conducted to assess staff awareness and experience in evidence-based practice.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
20
0
2
Order By: Relevance
“…In this study, some centers participating in the survey reported increased episiotomy rates, because each center had implemented its intervention with varied emphases on specific practices, depending on the perceived needs. They identified a number of barriers to the practice of restrictive episiotomy, which included: fear of tearing, difficulty in repairing lacerations compared to episiotomies, lack of preparation of the perineum, applicability of the research conducted in a different population, lack of time and the need to train the young/newer staff (14) . There was also a change in obstetric practice in a randomized controlled clinical trial with 600 nulliparous women in Iran comparing perineal protection techniques (hands onintervention technique of perineal protection and hands off -expectant technique of perineal protection) by the reduction of perineal traumas.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, some centers participating in the survey reported increased episiotomy rates, because each center had implemented its intervention with varied emphases on specific practices, depending on the perceived needs. They identified a number of barriers to the practice of restrictive episiotomy, which included: fear of tearing, difficulty in repairing lacerations compared to episiotomies, lack of preparation of the perineum, applicability of the research conducted in a different population, lack of time and the need to train the young/newer staff (14) . There was also a change in obstetric practice in a randomized controlled clinical trial with 600 nulliparous women in Iran comparing perineal protection techniques (hands onintervention technique of perineal protection and hands off -expectant technique of perineal protection) by the reduction of perineal traumas.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that other factors play an important role. One experimental study showed that educating midwives about evidence with respect to perineal management may reduce the incidence of episiotomy and increase the intact perineum rate . Our results may generate a debate among midwives about the indications for performing an episiotomy.…”
Section: Discussionmentioning
confidence: 77%
“…Houve quedas na taxa de episiotomia e do trauma grave nas nulíparas (92,2% para 80,7% e 6,7% para 3,0%, respectivamente); além de aumento da frequência de períneo íntegro em nulíparas (1,7% para 8,0%). Os autores concluíram que uma intervenção educativa baseada na utilização de evidências científicas resulta em melhorias na prática da episiotomia e na redução da taxa de trauma perineal entre as mulheres nulíparas (HO et al, 2010).…”
Section: Discussionunclassified